Nanotechnological synergy of mangiferin and curcumin in modulating PI3K/Akt/mTOR pathway: a novel front in ovarian cancer precision therapeutics - Alharbi, Hanan M.; Alqahtani, Taha; Alamri, Ali H.; Kumarasamy, Vinoth; Subramaniyan, Vetriselvan; Babu, K. Suresh (Frontiers in Pharmacology, 2024)
Background: Ovarian cancer, colloquially termed the "silent killer" among gynecological malignancies, remains elusive due to its often-asymptomatic progression and diagnostic challenges. Central to its pathogenesis is the overactive PI3K/Akt/mTOR signaling pathway, responsible for various cellular functions, from proliferation to survival. Within this context, the phytochemical compounds mangiferin (derived from Mangifera indica) and curcumin (from Curcuma longa) stand out for their potential modulatory effects. However, their inherent bioavailability challenges necessitate innovative delivery systems to maximize therapeutic benefits.Objective: This study seeks to synergize the merits of nanotechnology with the therapeutic properties of mangiferin and curcumin, aiming to bolster their efficacy against ovarian cancer. Methods: Employing specific nanotechnological principles, we engineered exosomal and liposomal nano-carriers for mangiferin and curcumin, targeting the PI3K/Akt/mTOR pathway.Molecular docking techniques mapped the interactions of these phytochemicals with key proteins in the pathway, analyzing their binding efficiencies. Furthermore, molecular dynamics simulations, spanning 100 nanoseconds, verified these interactions, with additional computational methodologies further validating our findings. The rationale for the 100 nanoseconds time span lies in its sufficiency to observe meaningful protein-ligand interactions and conformational changes. Notably, liposomal technology provided an enhancement in drug delivery by protecting these compounds from degradation, allowing controlled release, and improving cellular uptake.